General Geographical Description Of Angor District (Eurasian Journal of History, Geography and Economics, 2021)
This article examines the general geographical description of Angor district of Surkhandarya region, which covers the economic and geographical location of the district, natural conditions and resources, development of industry, agriculture and other sectors.